Basomelanocytic Neoplasms: A Report of Two Similar Tumors With Divergent Treatments. (July 2020) - Ryan, Michael P.; Bennett, Daniel D.; Goodwin, Brandon P.; Kelly, Brent C.
Abstract : Abstract: Basomelanocytic neoplasms are tumors consisting of elements of both basal cell carcinoma and melanoma. These tumors are exceedingly rare and present a unique challenge as to how the melanoma component should be classified. Due to the paucity of cases, there are no clear-cut evidence-based guidelines as to how these tumors should be staged and which treatment options provide the optimal outcome. We present 2 separate patients with similar cases of colonizing basomelanocytic tumors that were treated in drastically different ways, highlighting the differing approaches to treatment. We discuss theses treatment modalities and the challenges inherent to diagnosing and treating basomelanocytic neoplasms.